The Cleridae and Thanerocleridae of eastern North America, with illustrated keys, updated distributions, and special emphasis on the Kentucky fauna - Chapman, Eric G.; Leavengood, John M.; Dupuis, Julian R. (Zootaxa, 2025)
Species of Cleridae and Thanerocleridae in North America can be challenging to identify; with the exception of dichotomous keys in a handful of recent generic revisions, the few published keys for portions of this region are outdated and not well illustrated, and many taxonomic changes have occurred since their publication dates. To address this, we first compiled a list of 62 clerid and three thaneroclerid species occurring in eastern North America by examining thousands of specimens from dozens of collections with significant holdings of these taxa and combing the literature. We present fully illustrated dichotomous keys that will make identification relatively straightforward, even by those with little experience. For each species, we document its distribution (including 142 new state, 5 new provincial, and 2 new country records), and summarize its natural history, chemical attractants, mimicry and other pertinent information. Because the fauna of Kentucky is generally underreported, we put special emphasis on the fauna of the state and report detailed records for each of the 34 species for which we examined specimens, including 11 new state records. Phyllobaenus dubius (Wolcott, 1912) and P. iownesis (Chapin, 1922) are designated junior synonyms of P. pubescens (LeConte, 1849), new synonymies. Our over-arching goal for this paper is to be the launch pad for research involving clerids and thaneroclerids in eastern North America by facilitating species identification and presenting detailed biological information for each.